Implementasi Metode 36 Jam Dalam Pembelajaran Nahwu Sharaf Di Mahad Tahfizhil Quran Yayasan Islamic Centre Sumatera Utara - Alhammam, Ahmad Affan (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine the implementation of the 36 Hour method in learning nahwu sharaf at the Mahad Tahfizhil Quran Islamic Center Foundation, North Sumatra. The method used in this research is a qualitative research method. Qualitative research was carried out through the preliminary, preparation, implementation, and reporting stages. Data collection was carried out using interviews, observations, and documentation in the field. The data analysis technique carried out in this study was a qualitative description analysis. The results of his research are that in the implementation of the 36 Hours method there is preparation in its implementation. At the implementation stage, the 36 hour method for nahwu sharaf learning is carried out in formal and extracurricular classes. The implementation of the 36 hour method is considered quite effective in increasing students' understanding of nahwu sharaf learning. Factors supporting the 36 Hour method are the presence of professional teachers in the field of nahwu sharaf, support from the foundation, excellent facilities and infrastructure that make students comfortable learning and students' interest in continuing their studies abroad such as Egypt, Yemen, Saudi Arabia, Etc. And the inhibiting factor is the interest and motivation of students to learn nahwu sharaf, in short the learning hours provided by the mahad.